Sexual orientation discrimination in the labor market against gay men - Nick Drydakis (Global Labor Organization (GLO), 2021)
The study replicates the first European field experiment on gay men's labor market prospects in Greece. Utilizing the same protocol as the original study in 2006-2007, two follow-up field experiments took place in 2013-2014 and 2018-2019. The study estimated that gay men experienced occupational access constraints and wage sorting in vacancies offering lower remuneration. It was found that in 2013-2014 and 2018-2019, gay men experienced increasingly biased treatment compared to 2006-2007. Moreover, the results suggested that unemployment bore an association with occupational access constraints and wage sorting in vacancies offering lower remuneration for gay men. In each of the three experiments, this study captured recruiters' attitudes toward gay men. A one standard deviation increase in taste-discrimination attitudes against gay men decreased their access to occupations by 9.6%. Furthermore, a one standard deviation increase in statistical-discrimination attitudes against gay men decreased their access to occupations by 8.1%. According to the findings, in 2013-2014 and 2018-2019, firms excluding gay applicants expressed a higher level of taste- and statistical-discrimination attitudes compared to 2006-2007. A gay rights backlash due to the LGBTIQ+ group's attempt to advance its agenda, rising far-right rhetoric, and prejudice associated with economic downturns experienced in Greece might correspond with increasing biases against gay men.
Keywords: C93; J7; J16; J31; J42; J64; J71; J83; 330; Field experiment; Sexual orientation; Hiring discrimination; Wage sorting; Replication; Backlash; Unemployment; Economic recession